The Evolution of Gay Imagery in Mexican Cinema : an Analysis of Thirty-Six Films, 1970-1999. - Schulz-Cruz, Bernard (Edwin Mellen Press, 2010)
This book explores the accommodations made by the eye of the camera in its search for a homosexual body and gay identity. An analysis of Mexican movies produced during the last third of the 20th century reveals the emergence, the evolution, the articulation, the subversion and the liberation of gay images in Mexican cinema, but also a necessary addition for the full understanding those images in the context of changing Mexican society. The existing studies surrounding homosexuality in Mexican cinema criticize the stereotypical representations of the gay personality. What has not been consciousl.